Determination of pH value and Vitamin C Levels in Spontaneous Fermented Kimchi and Pickles by Acid Lactic Bacteria - Suleman, Dininurilmi; Rizki, Prajwalita Rukmakharisma; Susanto, Fika; Rahmawati, Ayu; Zhulaikah, Hanif Nur; Aulia, Maulida; Puspitasari; Firdaus, Nova Novia; Ajeng, Shavira; Hapsari, Alifia Karina (Fakultas Pertanian Universitas Veteran Bangun Nusantara, 2025)
Fermentation is the process of chemical transformation in an organic substrate through the activity of enzymes produced by microorganisms. Food fermentation provides some nutritional benefits. It also helps to maintain and increase the nutritional value of food such as vitamin C. Vitamin C, which satisfies the nutritional needs of a balanced diet, is found in abundance in fruits and vegetables. However, there is currently no preservation method that can maintain the amounts of ascorbic acid that are initially found in fruits and vegetables. This study aims to determine the effect of Vitamin C on pickle and kimchi fermentation process on some vegetable (red chilli, cucumber, water pumpkin and chinese cabbage). The result of analysis showed red chili pickle and cucumber pickle with no salt addition have vitamin C of 42.50 ± 2.07 mg/100gr and 16.13 ± 1.06 mg/100gr, respectively, while with 2.5% salt addition has vitamin C of 29.30 ± 4.14 mg/100gr and 8.80 ± 0.70 mg/100gr, respectively. While water pumpkin kimchi and Chinese cabbage kimchi with no salt addition have vitamin C of 20.50 ± 1,65 mg/100gr and 20.50 ± 0.71 mg/100mg, while kimchi and Chinese cabbage with 2.5% salt addition have vitamin C of 25.81 ± 2,30 mg/100gr and 34.12 ± 1.48 mg/100gr, respectively. Therefore, it showed that the addition of salt ingredient on red chili and cucumber pickle might reduce the vitamin C levels, while it might increase the vitamin C levels of water pumpkin and Chinese cabbage kimchi. Keywords: fermentation, kimchi, pickle, vegetable, vitamin C